Formative research for mhealth HIV adherence: the iHAART app - Rosen, Rochelle K. (Proc Annu Hawaii Int Conf Syst Sci, 2015)
Qualitative research was conducted to adapt and develop an mHealth app for HIV patients with histories of substance abuse. The app provides reactive, visual representations of adherence rates, viral load and CD4 counts. Two sets of focus groups were conducted with 22 participants. The first concentrated on use of reminder system and opinions about ideal adherence features. Results informed adaptation of an existing system, which was then presented to participants in the second set of focus groups. We describe participant responses to candidate app characteristics and their understanding of the HIV disease state based on these changing images. Qualitative results indicate that a balance of provided and requested information is important to maintain interest and support adherence. App characteristics and information can provoke positive and negative reactions and these emotional responses may affect adherence. Conclusion: User understanding of, and reaction to, app visual content was essential to adaptation and design.